ENHANCING RISK-ADJUSTED RETURNS FOR RETAIL INVESTORS: AN EXPLORATION OF DUAL MOMENTUM STRATEGIES IN GLOBAL SECTOR ETF INVESTING - Pavlović, Danica; Korenak, Boris; Stakić, Nikola (The European Journal of Applied Economics, 2025)
Investment performance evaluation is essential in determining the effectiveness of investment strategies, as it enables investors to assess risk-adjusted returns and benchmark performance against traditional indices. The rapid development of financial products has significantly expanded the range of investment opportunities, enabling investors to achieve their objectives in ways that were previously not possible. However, the sheer volume of available alternatives introduces considerable complexity into the decision-making process. While institutional investors can mitigate these challenges by developing specialized expertise, such resources are often inaccessible to retail investors. In response, market index ETFs (exchange-traded funds) have become a widely adopted, cost- and time-efficient investment vehicle, offering broad market exposure, diversification, and simplicity, typically without the need for advanced analysis. While this approach may suffice for many investors, there is potential for retail investors to enhance risk-adjusted returns through more refined strategies. This study investigates the application of dual-momentum strategies, which involve leveraging the performance of global sector ETFs and incorporating a “flight-to-safety” mechanism when market conditions dictate. The findings suggest that such strategies can deliver superior risk-adjusted performance relative to traditional index investing via ETFs.